Age-dependent immune response in pigs against foot-and-mouth disease virus in vitro - Jae-Hee Roh; Ngoc Anh Bui; Hu Suk Lee; Vuong Nghia Bui; Duy Tung Dao; Vu Thi Thanh; Hoang Thi Thuy; Kyoung-Min So; Seung-Won Yi; Eunju Kim; Tai-Young Hur; Sang-Ik Oh (Korean Society of Animal Science and Technology, 2021)
Foot-and-mouth disease, one of the most contagious diseases in cloven-hoofed animals, causes significant economic losses. The pathogenesis of foot-and-mouth disease virus (FMDV) infection is known to differ with age of the animals. In this study, we aimed to reveal the difference in immunological response in the initial stage of FMDV infection between piglets and adult pigs. Peripheral blood mononuclear cells (PBMCs) were isolated from 3 piglets (8 weeks old) and 3 pigs (35 weeks old) that were not vaccinated against FMDV. O-type FMDV (2 × 102 TCID50) was inoculated into porcine PBMCs and the cells were incubated at 37.0 °C under 5% CO2 for various time periods (0, 1, 3, 6, 12, 24, and 48 h). The total RNA was obtained from the FMDV-inoculated PBMCs after each time point, and the virus titer was investigated in these RNA samples. Furthermore, dynamics of mRNA expression of the six tested cytokines (IFN-α, IFN-γ, IL-6, IL-8, IL-10, and TNF-α) in FMDV-inoculated porcine PBMCs were evaluated by time-series analysis to determine the differences, if any, based on the age of the pigs. The PBMCs of piglets contained the highest quantity of FMDV mRNA at 6 h post-inoculation (hpi), and the PBMCs of pigs had the highest quantity of FMDV mRNA at 3 hpi. The mean cycle threshold-value in the PBMCs steadily decreased after the peak time point in the piglets and pigs (6 and 3 hpi, respectively). The dynamics of mRNA expression of all cytokines except TNF-α showed age-dependent differences in FMDV-inoculated PBMCs. The mRNA expression of most cytokines was more pronounced in the piglets than in the pigs, implying that the immune response against FMDV showed an age-dependent difference in pigs. In conclusion, within 48 hpi, the 8-week-old piglets responded more rapidly and were more sensitive to FMDV infection than the 35-week-old pigs, which could be associated with the difference in the pathogenesis of FMDV infection among the pigs. These results provide valuable insights into the mechanisms underlying the age-dependent differences in immune response in pigs against FMDV infection.